Intelligent Transportation System Protocol Interoperability Evaluation - Jonas Vogt; Hans D. Schotten; Horst Wieker (IEEE Open Journal of Intelligent Transportation Systems)
For decades, systems in the mobility sector have been maintained as discrete entities. It is imperative that they collaborate in order to enhance traffic safety and efficiency, while simultaneously reducing environmental pollution. The protocols employed in the formally separated ecosystems demonstrate disparate behaviors and data representations. In order to facilitate connectivity between these ecosystems, we propose the introduction of the Intelligent Transportation System Protocol Interoperability Evaluation (ITS-PIE). The evaluation method allows system architects and developers to analyze existing protocols in a six-step process. The initial step is the assessment of interdependencies, which identifies any formal or informal correlation between two protocol specifications. The second step is the formal classification of the protocols’ informal and formal descriptions, which emphasizes the specification’s similarities and differences. The formal comparison calculates the consensual parallelisms between the formal specifications. The data evaluation defines tooling to describe the specifications in a way that an automated transition can be conducted. The protocols’ architecture context evaluation displays the framework conditions. The final step is a situation-dependent interpretation. Two illustrative examples are provided herein to illustrate the advantages of the evaluation and to highlight the principal challenges that arise during the process.